Health, Social and Culture Value of Food Trading Based on Angkringan in Bogor West Java - Bahagia Bahagia; Leny Muniroh; Fachruddin Majeri Mangunjaya; Rimun Wibowo; Zakky Muhammad Noor; Abdul Karim Halim (Universitas Pahlawan Tuanku Tambusai, 2022)
Culture and traditions have started to become extinct so it needs to be investigated further to save the values of tradition and culture. This study aims to find social and cultural capital as well as the economic value of angkringan. The research method used is descriptive qualitative method. While the sampling was done by purposive technique. The results showed that there were social values in the angkringan culinary tradition because the traders or owners interacted socially with consumers from various groups. Even consumers between consumers can say hello and between consumers and angkringan owners. In addition, there is the value of mutual help because the prices of food and drinks at angkringan are very affordable so that they can help consumers who lack funds during the Covid-19 period. In addition, there is a health value because the drinks served at angkringan include ginger drinks and wedang uwuh which are useful for maintaining health, especially during the covid-19 period. Then, angkringan is a cultural element that must be maintained through the traditional food and beverage. Angkringan also using social media to adapt the outbreak of covid-19. Lastly, to maintain the quality of the food, the cook should not change so that it does not change in terms of taste